Comparing of human resources management sports enterprises and the other service enterprises - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
The aim of this study is to emphasize the importance of human resources management at sports enterprises, which has an important part in business activities and to compare service enterprises except sports business with human resources management. Private hospitals have been chosen as service business. The answers have been reached by discussing with the directors of 45 successful private hospitals, 36 sports enterprises of Istanbul in person. With different reasons 34 of hospitals and 31 of sports enterprises have been taken into assessment. The questionnaire has been used as a means of data collection. At research. Mann Whitney U Test has been applied in data analysis. At survey, the affairs about human resources management functions have been examined in nine dimensions. These are human power planning, employee choice and placement, training and development, career planning, performance assessment, payment, protection, discipline and separation functions in order. It is concluded that considering sports business hospital's human resources managements application situation of human power planning and payment functions are low but all other functions application situation at hospitals are higher considering sports business. To the research conclusion it has been come out that sports enterprises and private hospitals human resources managements have similarities and the directors have given positive opinion. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: enterprice; service; human resources management